Eosinophilic gastrointestinal disease below the belt - Pesek, Robert D. (J Allergy Clin Immunol, 2019)
Eosinophilic gastrointestinal diseases (EGIDs) are rare diseases of the gastrointestinal tract caused by allergic inflammation and gastrointestinal dysfunction. Initially described in 1978, recognition of these disorders has greatly increased over the past several decades. Thus far, eosinophilic esophagitis (EoE) has received the most focus, leading to significant advances in understanding of disease mechanisms, widely adopted guidelines for diagnosis and management, and ongoing clinical trials to provide expanded treatment options. EGIDs can affect other parts of the gastrointestinal tract and include eosinophilic gastritis (EG), eosinophilic gastroenteritis (EGE), and eosinophilic colitis (EC), yet these diseases are barely understood compared with EoE. Much of the research to date is limited to case series or single-center experiences, and there are no well-established guidelines for diagnosis or management. In this article the current state of EGIDs will be reviewed.